Perancangan Multimedia Interaktif Percakapan Umum Tentang Traveling dalam Bahasa Korea sebagai Media Pembelajaran - yashinta puspita ayu (Jurnal Desain Komunikasi Visual Asia, 2019)
Korea is currently forming a new mainstream in various countries through K-pop (Korean pop music), drama series, films etc. The success of Korean pop culture is proven by the emergence of the term "The Korean Wave" as a form of expression of how much influence the pop culture has spread. By carrying out its Korean Waven culture, Korea has managed to attract a large number of tourists or travellers from various countries around the world to travel. But there are various kinds of obstacles that are often experienced by foreign travellers, one of which is language. Language is an important factor when traveling to Korea, for tourists who cannot speak Korean this is certainly an important obstacle. Although there are now many Korean language learning books and videos published, but they are not detailed, less interesting and only in the form of texts which often make it difficult to learn. Besides that, it is also seen when reading a word in Korean, most of them are still difficult to pronounce letters correctly so that the words they mention are mispronounced. It is on this basis that multimedia is chosen because it is easily accessible in today's technology, which can contain more detailed information about the Korean language and how to pronounce it to the public.